Language ENvironment Analysis Language and Autism Screen and the Child Development Inventory Social Subscale as a Possible Autism Screen for Children Who Are Deaf or Hard of Hearing - Carr, Jason; Xu, Dongxin; Yoshinaga-Itano, Christine (Seminars in Speech and Language, 2014)
The Language ENvironment Analysis Language and Autism Screen (LLAS) is an automated vocal production analysis that has been shown to be a valid screener for autism in hearing children between the ages of 24 to 48 months of age. Although there is reportedly a higher incidence of autism among children who are deaf or hard of hearing, the diagnosis of autism is usually later than that in children with hearing. None of the traditional screening instruments have been used with children with hearing loss. Data about the utility of LLAS with children who are deaf or hard of hearing will be presented and discussed. Though more data will be needed, an LLAS at-risk flag in conjunction with the Social Quotient from the Child Development Inventory holds significant promise for a screen for children who are deaf or hard of hearing.
Keywords: Deaf or hard of hearing; autism; screen; early childhood